CTRP13 Protects H9c2 Cells Against Hypoxia/Reoxygenation (H/R)-Induced Injury Via Regulating the AMPK/Nrf2/ARE Signaling Pathway. (29th July 2021) - Jiang, Weifeng; Song, Jungang; Zhang, Suitao; Ye, Yanyan; Wang, Jun; Zhang, Yilin
Myocardial infarction (MI) is identified as the myocardial necrosis due to myocardial ischemia/reperfusion (I/R) injury and remains a leading cause of mortality. C1q/TNF-related protein 13 (CTRP13) is a member of CTRP family that has been found to be involved in coronary artery disease (CAD). However, the role of CTRP13 in MI remains unclear. We aimed to explore the functional role of CTRP13 in H9c2 cells exposed to hypoxia/reoxygenation (H/R). Our results demonstrated that H/R stimulation significantly decreased the expression of CTRP13 in H9c2 cells. H/R-induced an increase in ROS production and reductions in activities of SOD and CAT were prevented by CTRP13 overexpression but were aggravated by CTRP13 silencing. Moreover, CTRP13 overexpression could reverse the inductive effect of H/R on caspase-3 activity and bax expression, as well as the inhibitory effect of H/R on bcl-2 expression in H9c2 cells. However, CTRP13 silencing presented opposite effects with CTRP13 overexpression. Furthermore, CTRP13 overexpression enhanced the H/R-stimulated the expression levels of p-AMPK and nuclear Nrf2, and Nrf2 transcriptional activity. However, inhibition of AMPK reversed the CTRP13-mediated activation of Nrf2/ARE signaling and the cardiac-protective effect in H/R-exposed H9c2 cells. Additionally, silencing of Nrf2 reversed the protective effects of CTRP13 against H/R-stimulated oxidative stress and apoptosis in H9c2 cells. Finally, recombinant CTRP13 protein attenuated myocardial I/R-induced injury in rats. Taken together, these findings indicated that CTRP13 protected H9c2 cells from H/R-stimulated oxidative stress and apoptosis via regulating the AMPK/Nrf2/ARE signaling pathway. Our results provided evidence for the therapeutic potential of CTRP13 in myocardial I/R injury.